MANAGEMENT OF ENDOCRINE DISEASE: Outcome of adrenal sparing surgery in heritable pheochromocytoma. Issue 1 (January 2016) - Castinetti, F; Taieb, D; Henry, J F; Walz, M; Guerin, C; Brue, T; Conte-Devolx, B; Neumann, H P H; Sebag, F
Abstract : The management of hereditary pheochromocytoma has drastically evolved in the last 20 years. Bilateral pheochromocytoma does not increase mortality in MEN2 or von Hippel-Lindau ( VHL ) mutation carriers who are followed regularly, but these mutations induce major morbidities if total bilateral adrenalectomy is performed. Cortical sparing adrenal surgery may be proposed to avoid definitive adrenal insufficiency. The surgical goal is to leave sufficient cortical tissue to avoid glucocorticoid replacement therapy. This approach was achieved by the progressive experience of minimally invasive surgery via the transperitoneal or retroperitoneal route. Cortical sparing adrenal surgery exhibits <5% significant recurrence after 10 years of follow-up and normal glucocorticoid function in more than 50% of the cases. Therefore, cortical sparing adrenal surgery should be systematically considered in the management of all patients with MEN2 or VHL hereditary pheochromocytoma. Hereditary pheochromocytoma is a rare disease, and a randomized trial comparing cortical sparing vs classical adrenalectomy is probably not possible. This lack of data most likely explains why cortical sparing surgery has not been adopted in most expert centers that perform at least 20 procedures per year for the treatment of this disease. This review examined recent data to provide insight into the technique, its indications, and the results and subsequent follow-up in the management of patients with hereditary pheochromocytoma with a special emphasis on MEN2.